Climate risk perception and ex-ante mitigation strategies of rural households in Thailand and Vietnam - Marc Völker; Songporne Tongruksawattana; Bernd Hardeweg; Hermann Waibel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
A major risk factor for rural areas in emerging market economies, such as Thailand and Vietnam, can be attributed to climate change. Adoption of effective ex-ante mitigation strategies is a function of socio-economic household and location characteristics including, among others, the decision makers' perceptions of risk. This study aims to analyze both the determinants of climate-related risk perception and its influence on the choice of ex-ante mitigation strategies. In the context of the DFG research project Impact of Shocks on the Vulnerability to Poverty: Consequences for Development of Emerging Southeast Asian Economies, data were collected in a panel survey among some 4,400 rural households in 2007 and 2008 in six peripheral provinces in Thailand and Vietnam. Methodologically a three-step regression approach is applied. In the first step households' risk perception is explained. The second step is to assess general adoption of risk mitigation actions. In the third step the likelihood of households taking up particular ex-ante risk management strategies is established. Initial results show that rural households are particularly concerned about climate risk. However, the majority of households do not undertake any activity to mitigate risks ex-ante. The experience of climate shocks increases risk perception while other factors are also identified as significant determinants. For those who adopt preventive measures households in Vietnam particularly pre-adjust for storms while Thai households accommodate especially for drought. Findings are expected to be useful for the development of risk management strategies for rural households when differences in risk perception are taken into account.
Keywords: 330